Pengaruh Pemahaman Pajak dan Pengetahuan Pajak Terhadap Kepatuhan Wajib Pajak UMKM - Indrawan, Rizki; Binekas, Bani (Jurnal Riset Akuntansi dan Keuangan, 2018)
The purpose of this study is to determine the influence of understanding and knowledge of tax on SME taxpayer compliance. The research method used is the explanatory method. The population in this study is the SMEs in Cimahi City with the number of sample of 200 respondents. The sampling technique used is a simple random sampling. The data retrieval technique used is a questionnaire by using Likert instrument measuring scale. Data analysis technique used is Multiple Linear Regression. The results showed that there is a positive influence of understanding of taxes and tax knowledge variables on the taxpayer compliance of SMEs in Cimahi City.